Development Of Strength Physical Qualities Of Students Based On Rotary Movement Exercises (Eurasian Journal of Learning and Academic Teaching, 2022)
In the article, it has been proven that the strength based on rotational movement exercises has a reliable effect compared to the physical exercises specified in the training program for the development of physical qualities.